Acoustic emission and the Portevin-Le Châtelier effect in tensile tested Al alloys processed by ARB technique - PAWEŁEK, Andrzej; KUŚNIERZ, Jan; BOGUCKA, Joanna; JASIEŃSKI, Zdzisław; RANACHOWSKI, Zbigniew; RANACHOWSKI, Przemysław; REJMUND, Feliks; DĘBOWSKI, Tomasz (Archives of Acoustics, 2014)
The paper presents the investigations of the relation between the acoustic emission (AE) and the Portevin-Le Châtelier (PL) phenomena occurring in tensile tested two kinds of aluminium alloys: not-predeformed and predeformed earlier using the technique of accumulative rolling banding (ARB). There have been found essential correlations between AE and PL effects in ARB not-predeformed alloys. The tensile tests for ARB predeformed alloys were performed on a series of samples of various degree of work hardening and it has been observed that the correlations between the AE and PL effects are not so pronounced as in the case of ARB not-predeformed alloys. The results of AE measurements obtained using a new software allowed additionally to carry out the spectral analysis of AE signals and, in consequence, to determine the acoustic maps (acoustograms) and the spectral characteristics which are very useful in the discussion of the relations between the non-homogeneous strain mechanisms of the PL effect and the mechanisms of AE events generation. The results are discussed in the context of the existing dislocation models of the PL effect and the theoretical concepts of AE sources.